Preparation method of graphene / phase change composite material with gradient structure

By designing a gradient pore size structure in graphene/phase change composite material, the problem of insufficient thermal conductivity and charge and release time in the prior art is solved, and more efficient thermal management performance is achieved.

CN119490822APending Publication Date: 2025-02-21TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311035105.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing phase change composite materials have shortcomings in thermal conductivity and charge and release time, especially the anisotropy and temperature gradient of the pore structure limit their thermal management performance.

Method used

By regulating the gradient pore size structure in the graphene/phase change composite, the porosity close to the heat source end is high so as to fill more phase change molecules and the porosity away from the heat source end is small to ensure the main heat transfer effect of the graphene framework. The method includes hydrothermal preparation of graphene hydrogels, ice template method for preparation of graphene aerogels, and "welding" by spraying graphene oxide and hydrazine hydrate, and finally filling the phase-changing molecules by vacuum impregnation.

Benefits of technology

It realizes rapid heat absorption near the heat source and sufficient heat conduction channels away from the heat source, thereby improving the heat utilization of phase-change composite materials and shortening the charging and discharging time, improving the thermal management performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490822A_ABST
    Figure CN119490822A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a graphene / phase change composite material with a gradient structure. The preparation process comprises the following four parts: firstly, preparing graphene hydrogel with different porosities by a hydrothermal method; then putting the obtained graphene hydrogel into a quartz mold of which the bottom is in contact with copper plates with different pre-freezing temperatures by utilizing an ice template method, freezing water in the hydrogel from bottom to upper surface, and enabling ice crystals to vertically and radially grow from the bottom; freeze-drying the graphene aerogel in a freeze-drying machine to obtain graphene aerogel with different porosities and different pore diameters; a layer of graphene oxide solution is sprayed on the surface of aerogel needing welding, then a layer of hydrazine hydrate solution is sprayed, the two surfaces are tightly attached, and the integrated graphene aerogel with the gradient aperture structure is obtained after the solvent is naturally volatilized. In order to optimize the heat transfer performance, the graphene aerogel with large porosity and large aperture should be placed on the bottom layer, and the graphene aerogel with small porosity and small aperture should be placed on the top layer; and finally, obtaining the graphene / phase change composite material with the gradient structure through a vacuum impregnation method. The gradient structure facilitates rapid heat absorption close to a heat source, has enough heat conduction channels far away from the heat source, and facilitates improvement of heat utilization of the phase change composite material, optimization of a heat transfer structure and shortening of heat charging and discharging time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a graphene / phase change composite material with a gradient structure, and belongs to the technical field of phase change composite materials. Background Art

[0002] As electronic products accelerate their development towards high power, high integration, thinness and intelligence, indicators such as integration, power density and assembly density continue to rise, placing higher requirements on the thermal management and heat dissipation capabilities of electronic devices. To avoid device failure caused by overheating, technologies such as thermal grease, thermal gel, graphite thermal conductive sheet, heat pipe and heat spreader have emerged one after another.

[0003] Organic phase change materials (PCMs) have the advantages of high phase change enthalpy, suitable phase change temperature, near isothermal phase change process, low cost, and long service life, and have been widely used in the field of thermal management of electronic products. However, the low thermal conductivity of organic phase change molecules has become the key to limiting the performance of phase change materials. Under low thermal conductivity, the heat transfer capacity of phase change materials is poor and the heat charging and discharging time is long. In order to improve this shortcoming, porous materials with high thermal conductivity are usually introduced for material composite. Commonly used porous substrates for phase change composite materials include expanded graphite, foamed metal, carbon foam, aluminum nitride aerogel, polyimide aerogel, and graphene aerogel. These porous materials provide a place for the adsorption of phase change molecules on the one hand, and provide a continuous skeleton for heat conduction on the other hand. Among them, graphene aerogel stands out because of its low density, strong adsorption capacity, high porosity, good mechanical properties, and good thermal conductivity. The ice template method can use easily removable ice crystals as templates. The ice crystals nucleate on the surface of the cold source and grow along the temperature gradient to produce a porous material with radial pores. The pore size can be controlled according to the cold source temperature and is suitable for the preparation of porous materials.

[0004] Although the porous thermal conductive framework can improve the thermal conductivity of the phase change material (κPCM), there is still a limitation that the pore structure is anisotropic and there is a temperature gradient inside the phase change material. Therefore, it is of great significance to design and prepare a graphene / phase change composite material with a gradient structure, in which the phase change material near the heat source end is the main part and the thermal conductive framework far away from the heat source end is the main part, by regulating the pore structure perpendicular to the heat source direction in the graphene phase change composite material. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a graphene / phase change composite material with a gradient structure. The graphene / phase change composite material with a gradient pore size structure has a large porosity on the side contacting the heat source so as to fill more phase change molecules, and a small porosity on the side away from the heat source. The graphene skeleton plays a major role in heat transfer, thereby making up for the shortcomings of the phase change molecules, such as poor thermal conductivity and long heat charging and releasing time.

[0006] The present invention adopts the following technical solution:

[0007] The present invention relates to a method for preparing a graphene / phase change composite material with a gradient structure, and the steps are as follows:

[0008] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. Graphene oxide solutions of different concentrations were prepared and dispersed evenly by ultrasonication using a cell crusher. The evenly dispersed solution was placed in a hydrothermal reactor and subjected to hydrothermal reaction in an oven to obtain graphene hydrogels with different porosities.

[0009] 2) Preparation of graphene aerogel: The graphene hydrogel obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate of different pre-freezing temperatures, and the water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying to obtain graphene aerogels with different porosities and pore sizes.

[0010] 3) "Welding" of aerogel: Spray a layer of graphene oxide solution on the top or bottom surface of the graphene aerogels with different porosities and pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and tightly fit the two surfaces to be welded. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained. In order to optimize the heat transfer performance, the graphene aerogel with large porosity and large pore size should be placed on the bottom layer; the graphene aerogel with small porosity and small pore size should be placed on the top layer.

[0011] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in an organic phase change material, and adsorbed by a vacuum impregnation process to obtain a graphene / phase change composite material.

[0012] Preferably, the concentration of the graphene oxide solution in step 1) is 4-7 mg / ml.

[0013] Preferably, in step 1), the oven temperature is 110-150° C., and the hydrothermal reaction time is 12-16 h.

[0014] Preferably, the temperature of the pre-frozen copper plate in step 2) is -30 to -100°C.

[0015] Preferably, the freeze-drying time in step 2) is 36 to 72 hours.

[0016] Preferably, the concentration of the graphene oxide solution sprayed in step 3) is 8 to 14 mg / ml.

[0017] Preferably, the phase change material in step 4) can be paraffin, fatty amine, fatty acid, polyol, etc.

[0018] The present invention prepares several graphene oxide aerogels with different pore sizes by hydrothermal method and ice template method, sprays a layer of graphene oxide solution on the surface of the aerogel that needs to be "welded", then sprays a layer of hydrazine hydrate solution and tightly fits the two surfaces, and waits for the solvent to evaporate naturally to obtain an integrated graphene aerogel with a gradient pore structure. Finally, a graphene / phase change composite material with a gradient structure is obtained by vacuum impregnation. The gradient structure is conducive to rapid heat absorption near the heat source, and there are sufficient heat conduction channels away from the heat source, which is conducive to improving the utilization of heat by the phase change composite material and shortening the charging and discharging time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the graphene aerogel structure with gradient pore size

[0020] Figure 2 Microscopic orientation structure of graphene aerogel

[0021] Figure 3 Scanning electron microscope image of the pore structure of graphene aerogel DETAILED DESCRIPTION

[0022] Six embodiments of the present invention are given below to further illustrate the present invention, but not to limit the scope of the present invention.

[0023] Example 1

[0024] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 12 mg of freeze-dried graphene oxide powder and 1.30 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 15 mg of freeze-dried graphene oxide powder and 1.65 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent and dispersed evenly by ultrasonication using a cell crusher. The evenly dispersed graphene oxide solution (with a concentration of 4 mg / ml and 6 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 110°C for 12 hours to obtain graphene hydrogel.

[0025] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 4 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -60°C; in the same step, the graphene hydrogel with a concentration of 6 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -90°C. The water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 36 hours to obtain graphene aerogels with different porosities and pore sizes.

[0026] 3) "Welding" of aerogel: Spray a layer of graphene oxide solution with a concentration of 8 mg / ml on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), and then spray a layer of hydrazine hydrate for reduction. Press the two surfaces to be welded tightly for 1 hour, and after the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0027] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in n-octacosane and adsorbed by a vacuum impregnation process at 70° C. for 1 h to obtain a gradient graphene / phase change composite material.

[0028] Example 2

[0029] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 12 mg of freeze-dried graphene oxide powder and 1.30 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 21 mg of freeze-dried graphene oxide powder and 2.25 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent, and ultrasonically dispersed for 20-30 seconds using a cell crusher. The uniformly dispersed graphene oxide solution (concentration of 4 mg / ml and 7 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 120°C for 13 hours to obtain graphene hydrogel.

[0030] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 4 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -50°C; in the same step, the graphene hydrogel with a concentration of 7 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -90°C. The water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 48 hours to obtain graphene aerogels with different porosities and pore sizes.

[0031] 3) "Welding" of aerogel: Spray a layer of 10 mg / ml graphene oxide solution on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and press the two surfaces to be welded tightly for 2 hours. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0032] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in n-triacontane and adsorbed by a vacuum impregnation process at 80° C. for 1.5 h to obtain a gradient graphene / phase change composite material.

[0033] Example 3

[0034] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 15 mg of freeze-dried graphene oxide powder and 1.65 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 18 mg of freeze-dried graphene oxide powder and 1.95 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent, and ultrasonically dispersed for 20-30 seconds using a cell crusher. The uniformly dispersed graphene oxide solution (concentration of 5 mg / ml and 6 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 120°C for 14 hours to obtain graphene hydrogel.

[0035] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 5 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -70°C; in the same step, the graphene hydrogel with a concentration of 6 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -90°C. The water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 48 hours to obtain graphene aerogels with different porosities and pore sizes.

[0036] 3) "Welding" of aerogel: Spray a layer of 10 mg / ml graphene oxide solution on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and press the two surfaces to be welded tightly for 3 hours. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0037] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in octadecylamine and adsorbed by a vacuum impregnation process at 50° C. for 1.5 h to obtain a gradient graphene / phase change composite material.

[0038] Example 4

[0039] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 15 mg of freeze-dried graphene oxide powder and 1.65 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 21 mg of freeze-dried graphene oxide powder and 2.25 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent, and ultrasonically dispersed for 20-30 seconds using a cell crusher. The uniformly dispersed graphene oxide solution (concentration of 5 mg / ml and 7 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 130°C for 14 hours to obtain graphene hydrogel.

[0040] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 5 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -50°C; in the same step, the graphene hydrogel with a concentration of 7 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -90°C. The water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 60 hours to obtain graphene aerogels with different porosities and pore sizes.

[0041] 3) "Welding" of aerogel: Spray a layer of 12 mg / ml graphene oxide solution on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and press the two surfaces to be welded tightly for 3 hours. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0042] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in erythritol, and adsorbed by a vacuum impregnation process at 130° C. for 2 h to obtain a gradient graphene / phase change composite material.

[0043] Example 5

[0044] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 12 mg of freeze-dried graphene oxide powder and 1.30 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 15 mg of freeze-dried graphene oxide powder and 1.65 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 21 mg of freeze-dried graphene oxide powder and 2.25 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent, and ultrasonically dispersed for 20-30 seconds using a cell crusher. The uniformly dispersed graphene oxide solution (concentrations of 4 mg / ml, 5 mg / ml and 7 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 140°C for 15 hours to obtain graphene hydrogel.

[0045] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 4 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -40°C; in the same steps, the graphene hydrogel with a concentration of 5 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -60°C; in the same steps, the graphene hydrogel with a concentration of 7 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -80°C. The water in the hydrogel is frozen as ice fingers growing from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 60 hours to obtain graphene aerogels with different porosities and pore sizes.

[0046] 3) "Welding" of aerogel: Spray a layer of 12 mg / ml graphene oxide solution on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and press the two surfaces to be welded tightly for 4 hours. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0047] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in n-triacane and adsorbed by a vacuum impregnation process at 70° C. for 2.5 h to obtain a gradient graphene / phase change composite material.

[0048] Example 6

[0049] 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. 12 mg of freeze-dried graphene oxide powder and 1.30 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 18 mg of freeze-dried graphene oxide powder and 1.95 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent; in the same steps, 21 mg of freeze-dried graphene oxide powder and 2.25 mg of ascorbic acid were dissolved in 3 ml of DMSO solvent, and ultrasonically dispersed for 20-30 seconds using a cell crusher. The uniformly dispersed graphene oxide solution (concentrations of 4 mg / ml, 6 mg / ml and 7 mg / ml) was placed in a hydrothermal autoclave and reacted in an oven at 150°C for 16 hours to obtain graphene hydrogel.

[0050] 2) Preparation of graphene aerogel: The graphene hydrogel with a concentration of 4 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -30°C; in the same steps, the graphene hydrogel with a concentration of 6 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -60°C; in the same steps, the graphene hydrogel with a concentration of 7 mg / ml obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at a pre-freezing temperature of -90°C. The water in the hydrogel is frozen as ice fingers growing from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying for 72 hours to obtain graphene aerogels with different porosities and pore sizes.

[0051] 3) "Welding" of aerogel: Spray a layer of 14 mg / ml graphene oxide solution on the top or bottom surface of the graphene aerogel with different pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and press the two surfaces to be welded tightly for 5 hours. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained.

[0052] 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in n-octacosane and adsorbed by a vacuum impregnation process at 65° C. for 3 h to obtain a gradient graphene / phase change composite material.

Claims

1. A method for preparing a graphene / phase change composite material with a gradient structure, characterized in that The preparation steps are as follows: 1) Preparation of graphene hydrogel: Graphene hydrogel was prepared by hydrothermal method. Graphene oxide solutions of different concentrations were prepared, ultrasonically dispersed evenly by cell crusher and placed in a hydrothermal reactor, and hydrothermally reacted in an oven to obtain graphene hydrogels with different porosities; 2) Preparation of graphene aerogel: The graphene hydrogel obtained in step 1) is placed in a quartz mold whose bottom is in contact with a copper plate at different pre-freezing temperatures, and the water in the hydrogel is frozen into ice fingers that grow from top to bottom. The frozen hydrogel is then transferred to a freeze dryer for freeze drying to obtain graphene aerogels with different porosities and pore sizes. 3) "Welding" of aerogel: Spray a layer of graphene oxide solution on the top or bottom surface of the graphene aerogels with different porosities and pore sizes obtained in step 2), then spray a layer of hydrazine hydrate for reduction, and tightly fit the two surfaces to be welded. After the solvent evaporates naturally, a graphene aerogel with a gradient pore size structure is obtained. In order to optimize the heat transfer performance, the graphene aerogel with large porosity and large pore size should be placed on the bottom layer; the graphene aerogel with small porosity and small pore size should be placed on the top layer; 4) Filling of phase change molecules: The graphene aerogel with a gradient pore size structure obtained in step 3) is placed in an organic phase change material, and adsorbed by a vacuum impregnation process to obtain a graphene / phase change composite material.

2. The preparation method according to claim 1, characterized in that The concentration of the graphene oxide solution in step 1) is 4-7 mg / ml.

3. The preparation method according to claim 1, characterized in that In step 1), the oven temperature is 110-150° C., and the hydrothermal reaction time is 12-16 hours.

4. The preparation method according to claim 1, characterized in that The temperature of the pre-frozen copper plate in step 2) is -30 to -100°C.

5. The preparation method according to claim 1, characterized in that The freeze-drying time in step 2) is 36 to 72 hours.

6. The preparation method according to claim 1, characterized in that The concentration of the graphene oxide solution sprayed in step 3) is 8 to 14 mg / ml.

7. The preparation method according to claim 1, characterized in that In step 4), the phase change material can be paraffin, fatty amine, fatty acid, polyol, etc.

8. The graphene / phase change composite material with a gradient structure obtained by the preparation method according to claim 1, characterized in that It has a gradient porosity and pore size in the direction perpendicular to the heat source. The side in contact with the heat source has a large porosity so that more phase change molecules can be filled to quickly absorb heat. The porosity is small on the side away from the heat source, and the graphene skeleton establishes enough heat conduction channels, which can improve the phase change composite material's utilization of heat and shorten the charging and dissipating time.